EVALUATION OF THE WOUND HEALING ACTIVITY OF COMMELINA BENGHALENSIS LEAVES EXTRACT IN EXPERIMENTAL RATS: Pharmaceutical Science-Pharmacology - JOSHI, OM PRAKASH; SINGH, BALWAN; DR. D.C.P SINGH (International Journal of Life Science and Pharma Research, 2019)
Wound is still a worldwide health problem. Both conventional and synthetic drugs used in the treatment of wound are inadequate and sometimes they cause fatal side effects. In the absence of a reliable drug in modern medicine, there are a number of medicinal preparations in Ayurveda recommended for the treatment of wound. In view of severe undesirable side effects caused by synthetic agents, there is a growing need to follow systematic research methodology to evaluate the scientific basis for the traditional herbal medicines that are claimed to possess therapeutic effects. The benefits of herbal wound healing agents attract the researchers to evaluate their use in modern medicine and to minimize the undesirable or unpleasant effect of synthetic medicines. As we know, herbal medicines are natural in origin, safe to consume in the modern day many herbal plants like aloe, neem, turmeric, brahmi, senna, ashwagandha, asafetida, ginger, fennel, sankhpusphi, are extensively used in modern medicine and showed their potential benefits. Commelina benghalensis is a herbaceous plant growing throughout India. In our study we found that the methenolic extract of Commelina benghalensis shows significant increase in breaking strength of the skin and histopathological studies also shows increase in the number of macrophages . Various concentrations of mehenolic extract of Commelina benghalensis are used i.e 5% methenolic extract of Commelina benghalensis and 10% methenolic extract of Commelina benghalensis and both the concentration are shown to increase the breaking strength although 10 % methenolic extract shows more collegen fibres in histological section. Hence the present study is designed to evaluate wound healing of potential of Commelina benghalensis leaves in rats